The Middle English Creolization Hypothesis: Persistence, Implications, and Language Ideology - O’Neil, David (Studia Anglica Posnaniensia, 2019)
Bailey and Maroldt (1977) and Domingue (1977) were the first to argue that language contact during the Middle Ages between Old English and both Old Norse and Norman French resulted in linguistic creolization. This theory, known as the Middle English creolization hypothesis, implies that Middle English, and perhaps Modern English as well, should be classified as a creole. Though frequently discredited on historic, linguistic, and terminological grounds, the creolization hypothesis has attracted interest for longer than might be expected. This paper argues that the persistence of the hypothesis may be ideologically motivated. The first section examines connotations of the term “creole” and applies these connotations to an analysis of the initial presentations of the creolization hypothesis. The second and third section of the paper review and analyze the forty-year history of the debate, focusing separately on arguments for creolization (and koinezation) between Anglo-Norman French and Old Norse, respectively. The fourth and final section examines challenges presented by the concept of creole exceptionalism to common attitudes about language equality and the theory of Universal Grammar. It is argued that these issues attract greater interest when contextualized within a discussion of a “major” world language such as English than when creolization is understood as an atypical process restricted to “peripheral” languages such as Haitian Creole. This paper also references relevant political issues such as the current controversy among medievalists about the field’s historic lack of inclusivity.